Numerical Model Simulation of the Double-Roll Rotary Forging of Large Diameter Thin-Walled Disk - Zhongquan Yu (MDPI AG, 2021)
Double-roll rotary forging is an emerging plastic forming technology based on rotary forging. Owing to the advantages of being labor-saving, a small eccentric load, low noise and vibration, good uniformity, high surface quality, and material saving, it is very promising for the fabrication of large diameter thin-walled disks. To date, little relevant research on the double-roll rotary forging technology of large diameter thin-walled metal disks has been reported, and the deformation characteristic and the influence of three key parameters on the double-roll rotary forging process remain uninvestigated. Herein, a reasonable 3D rigid-plastic numerical model of the double-roll rotary forging of a disk workpiece is established under the Deform software environment. Based on the valid 3D numerical model, the deformation mechanism, and the effective laws of three key parameters (feed rate v of the lower die, rotational speed n of the upper die, and the initial temperature T of the disk workpiece) on the metal flow and force and power parameters in the double-roll rotary forging process have been explored. The research results provide valuable guidelines for a better understanding of double-roll rotary forging for the fabrication of large diameter thin-walled disks.